3D-Printed PCL-Based Scaffolds with High Nanosized Synthetic Smectic Clay Content: Fabrication, Mechanical Properties, and Biological Evaluation for Bone Tissue Engineering - Furtado ASA; Cunha MHS; Sousa LMR; Brito GC; Verde TFCL; Filgueiras LA; Sobral-Silva LA; Santana MV; Sousa GF; Santos FEP; Mendes AN; Figueredo-Silva J; et al. (International Journal of Nanomedicine)
André SA Furtado,1,* Manuel HS Cunha,1,* Luciana MR Sousa,1 Guilherme C Brito,1 Thiago FCL Verde,1 Livia Alves Filgueiras,2 Leonardo A Sobral-Silva,3 Moisés V Santana,1 Gustavo F Sousa,1 Francisco EP Santos,4 Anderson N Mendes,2 José Figueredo-Silva,5 Antônio LM Maia Filho,5 Fernanda R Marciano,1,4 Luana MR Vasconcellos,3 Anderson O Lobo1 1Interdisciplinary Laboratory for Advanced Materials (LIMAV), Materials Science and Engineering Graduate Program (PPGCM), Federal University of Piauí (UFPI), Teresina, PI, Brazil; 2Laboratory of Innovation in Science and Technology, Department of Biophysics and Physiology, Federal University of Piauí, Teresina, PI, Brazil; 3Institute of Science and Technology, São Paulo State University (UNESP), São Paulo, SP, Brazil; 4Department of Physics, Federal University of Piauí (UFPI), Teresina, PI, Brazil; 5Biotechnology Research Center - State University of Piauí, Teresina, PI, Brazil*These authors contributed equally to this workCorrespondence: Anderson O Lobo, Interdisciplinary Laboratory for Advanced Materials, UFPI - Federal University of Piaui, Teresina, Brazil, Email lobo@ufpi.edu.brBackground: The 3D printing of macro- and mesoporous biomimetic grafts composed of polycaprolactone (PCL) infused with nanosized synthetic smectic clay is a promising innovation in biomaterials for bone tissue engineering (BTE). The main challenge lies in achieving a uniform distribution of nanoceramics across low to high concentrations within the polymer matrix while preserving mechanical properties and biological performance essential for successful osseointegration.Methods: This study utilized 3D printing to fabricate PCL scaffolds enriched with nanosized synthetic smectic clay (LAP) to evaluate its effects on structural, chemical, thermal, mechanical, and degradative properties, with a focus on in vitro biological performance and non-toxicity. Scaffolds were created with varying proportions of PCL and LAP. Comprehensive characterization included scanning electron microscopy (SEM), X-ray diffraction (XRD), thermogravimetric analysis (TGA), Fourier-transform infrared spectroscopy (FTIR), mechanical testing, swelling analysis, and degradation studies. Biological performance was assessed through MTT assays (cell viability), alkaline phosphatase activity, histological analysis, and Raman spectroscopy, highlighting the scaffolds’ biocompatibility and potential applications in regenerative medicine.Results: The developed inks demonstrated excellent injectability, and the 3D-printed PCL/LAP scaffolds exhibited a microporous and rough structure, good structural fidelity, low degradability, thermal stability, and sufficient mechanical strength across all formulations. Intrinsic properties of the scaffolds revealed no cytotoxicity while enhancing bioactivity and promoting in vitro mineralization when cultured with mesenchymal stem cells in all analyzed groups. Notably, the high concentration of LAP within the PCL matrices did not induce in vitro cytotoxicity but rather stimulated in vitro mineralization and differentiation.Conclusion: This study demonstrated the feasibility of 3D printing PCL/LAP scaffolds with high concentrations of nanoceramics. Both in vitro and in vivo assays validated the regenerative potential of these scaffolds, emphasizing their efficacy as a promising approach for developing advanced biomimetic grafts.Keywords: grafting, polycaprolactone, bone tissue regeneration, synthetic smectic clay